EFEKTIVITAS KARUNIA JAWATAN PENGGEMBALAAN BERDASARKAN 1 PETRUS 5:1-4 DI GEREJA BETHEL TABERNAKEL KRISTUS ALFA OMEGA TIRTOYOSO - Zalukhu, Aman Strive; Tjahja, Soendoro; Taneo, Didasgil (JOURNAL of THEOLOGICAL STUDENTS, 2024)
This thesis aims to examine the level of effectiveness of the pastoral ministry gift based on 1 Peter 5:1-4 in Bethel Tabernacle Church of Christ Alfa Omega Tirtoyoso. How effective the grazing has been is the ultimate goal of this study. This research is included in quantitative research using samples. The results of this study state that the level of effectiveness of the pastoral ministry gift is in the very good or very effective category. This is evidenced by the value of 91% after passing the hypothesis test from the questionnaire that was distributed to 59 respondents.